2006
DOI: 10.1111/j.1525-1438.2006.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

COX-1 and COX-2 expression in stage I and II invasive cervical carcinoma: relationship to disease relapse and long-term survival

Abstract: COX-1 and COX-2 are members of the cyclooxygenase (COX) family, which influence tumor invasion and apoptosis. The objective of the study was to assess the relationship between COX-1 and COX-2 expression in early-stage disease and subsequent disease relapse and long-term survival. Women with FIGO stage I and II cervical carcinoma, younger than 50 years, treated between 1981 and 1990 were included. COX-1 and COX-2 expressions in the tumors were assessed by immunohistochemistry. COX-1 and COX-2 were expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Such findings are in keeping with recent studies by immunohistochemistry, which demonstrate staining of COX-l in thyroid tumors but not in normal thyroid tissue (7); over expression of COX-l was also found in ovarian (8) and cervical cancer (9)(10). Also, experiments on murine models of cancer underline that both isoforms are involved in the development of skin cancer (11).…”
Section: Discussionsupporting
confidence: 76%
“…Such findings are in keeping with recent studies by immunohistochemistry, which demonstrate staining of COX-l in thyroid tumors but not in normal thyroid tissue (7); over expression of COX-l was also found in ovarian (8) and cervical cancer (9)(10). Also, experiments on murine models of cancer underline that both isoforms are involved in the development of skin cancer (11).…”
Section: Discussionsupporting
confidence: 76%
“…By the literature search and careful evaluation, a total of 28 eligible studies5–11, 16–31, 38–42 were identified. Of the 28 studies,5–11, 16–31, 38–42 three articles6, 38, 41 were eliminated due to inadequate data for meta‐analysis. In four studies,10, 24, 25, 40 patients involved were overlapping, therefore only the study24 with more complete data was selected in the overall analysis; one study25 involving only SCC patients was used in the subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Beside, five studies,8, 16–19 which all came from another research group, were different in treatment, assay method (antibody), and scoring protocol employed, so all of them were included. Thus, 23 studies5, 7–9, 11, 16–31, 39, 42 with 1,477 patients which met our inclusion criteria were selected for our meta‐analysis finally (For an overview of the studies identified, and their main characteristics, see Table 1). Regarding treatment, generally, cervical cancer can be treated with either surgery, radiotherapy, chemotherapy or a combination of these treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations